2010
DOI: 10.1111/j.1440-1746.2010.06286.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of methylenetetrahydrofolate reductase G1793A, hyperhomocysteinemia, and folate deficiency correlate with ulcerative colitis in central China

Abstract: MTHFR G1793A gene polymorphism, HHcy, folate deficiency and low vitamin B(12) concentration were associated with ulcerative colitis in central China. Our findings demonstrate that the Hcy-related gene and metabolites are involved in pathogenesis of ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…The 12 studies included 2570 individuals in total, with 1086 IBD patients and 1484 controls [15,16,22,23,24,25,26,27,28,29,30,31]. The detailed results are expressed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 12 studies included 2570 individuals in total, with 1086 IBD patients and 1484 controls [15,16,22,23,24,25,26,27,28,29,30,31]. The detailed results are expressed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 12 studies, the folate concentration in the study by Kuroki et al [24] was excluded because it was detected in red blood cells. Folate and vitamin B12 were detected via chemiluminescence immunoassays in three studies [15,22,28], radioimmunoassays in four studies [23,24,25,30], ELISA in two studies [26,31], a specific immunochemical method in one study [29], and the IMx assay in one study [16]. Three studies did not include the mean age of patients and controls [15,16,23], and one study included the median age of patients and controls [23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperhomocysteinemia (HHcy) is defined as serum homocysteine level >15.0 μmol/L. Over the past decades, many studies have demonstrated that HHcy is pretty prevalent in blood circulation and intestinal mucosa of IBD patients and conducive to the development of IBD [8][9][10] .…”
mentioning
confidence: 99%